IMPROVING STUDENTS’ ABILITY TO IDENTIFY PARTS OF SPEECH THROUGH GRAMMAR TRANSLATION METHOD - A. Eritme Yustika Abrar; Sri Wahyuni Thamrin (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2020)
Abstract:The method of this research is Classroom Action Research that consists of two cycles. The objective of this research is intended to investigate the students’ ability and achievement to identify verb, noun and adjective in the sentences through Grammar Translation Method as a teaching media at the Second Semester Students of BulukumbaMuhammadiyah University. The subject of this research was 36 second semester students of class 19A of Bulukumba Muhammadiyah University. The instruments of this research are written test and observation sheet. The research findings show that the students’ scores in identifying parts of speech before implementing the Grammar Translation Method was 67.6 (fairly good), but after applying the method, the students’ score in the cycle I became 74.2 (good) and in the cycle II, the students’ score improved until 83.7 (Very Good). The students’ participation in the teaching and learning activities also improved every meeting, where in the first meeting of cycle I was 53.7% and then became 88.2% in the fourth meeting of cycle II.Abstrak:Metode penelitian ini adalah Classroom Action Research yang terdiri dari dua siklus. Tujuan penelitian ini dimaksudkan untuk mengetahui kemampuan dan prestasi mahasiswa untuk mengidentifikasi kata kerja, kata benda dan kata sifat dalam kalimat melalui Metode Penerjemahan Tata Bahasa sebagai media pengajar pada Mahasiswa Semester II Universitas Muhammadiyah Bulukumba). Subjek penelitian ini adalah angkatan 19A pada Mahasiswa Semester II Universitas Muhammadiyah Bulukumba yang terdiri dari 36 mahasiswa. Instrumen penelitian ini adalah tes tertulis dan lembar pengamatan. Temuan penelitian ini adalah nilai siswa untuk mengidentifikasi bagian-bagian pidato sebelum metode terjemahan tata bahasa aplikasi adalah 67,6 (cukup baik), tetapi setelah menerapkan metode skor siswa dalam siklus I menjadi 74,2 (baik) dan pada siklus II nilai siswa meningkat hingga 83,7 (Sangat Baik). Partisipasi siswa dalam mendengarkan pengajaran dan pembelajaran juga meningkatkan setiap pertemuan, di mana pada pertemuan pertama siklus I adalah 53,7% dan kemudian menjadi 88,2% dalam pertemuan keempat siklus II.